已知a²+b²=5,ab=-3,求代数式 -3(ab-a²-2b²)+2(a
1个回答
-3(ab-a²-2b²)+2(a²+3b²+ab)
=-3ab+3a²+6b²+2a²+6b²+2ab
=-ab+5a²+12b²
题目是错的,请核对题目.
相关问题
已知a-b=5,ab=3,求代数式a^3b-2a^2*b^2+ab^3
已知ab/a+b=5求代数式3a-5ab+3b/-2a+3ab-2b的值
已知a²-ab=3,ab+b²=-5,求代数式a²+b²与a²-2ab
已知a+b=5,ab=-3,求代数式(2a-3b-2ab)-(a-4b-ab)的值.
已知代数式(3a-ab+2b²)-(a²-5ab+b²)-2(a²+2ab+a&
已知(a-2)²+(b+1)²=0,求代数式3a²b+ab²-3a²b+5ab+ab²-4ab+1/2a²b
已知a+b=3,ab=—2,求代数式(3a+5ab)_(3ab_3b)的值
已知a-b=5,ab=-1,求代数式(2a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值.
已知a-b=5,ab=1,求代数式(2a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值.
已知a-b=5,ab=-1,求代数式(2a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值.